Red Jungle Fowl Offspring Maintenance System And Production In The Community In Bengkulu - Sutriyono, Sutriyono; Santoso, Urip; Putranto, Heri Dwi; Suherman, Dadang (BPFP Universitas Bengkulu, 2023)
The red junglefowl is a wild fowl and has been tamed and produces offspring, and is kept by the people of Bengkulu. The aim of the research is to identify and evaluate rearing management and production of red jungle fowl offspring in communities in Bengkulu. Research respondents were determined using the snowball sampling method, and fifty respondents were obtained. Data was obtained through observation, discussion and interviews, and filling in prepared forms; namely food management, housing, disease prevention, utilization and production. The results showed that the RJF offspring kept by the community were used for crossbreeding with local chickens (47%), production of chicks (28%), as hunting chickens (62%), and ornamental chickens (82%). Chickens are kept in 4 ways: (1) housed during the day and night, (2) chickens are kept free during the day and housed at night, (3) chickens are kept free at any time, and (4) chicken is placed on a perch. Feed given is commercial feed (BR1), corn, rice, brown rice, bran, crickets and ant eggs. Average egg production is 34 eggs/ hen/year, and chick production is estimated at 27 chicks/hen/year, and population growth is 2.68%/year. In conclusion, the community raising chicken is traditional, the quantity and quality of feed is not sufficient, the cages are very simple, disease prevention and safety protection are inadequate. As a local chicken, the average egg production is high, hatchability and chick production are high, but population development is slow. Poor chick rearing management and the aim of raising RJF offspring cause population development to be slow. Keywords: Community, management and production, rearing, RJF Offspring ABSTRAK Ayam hutan merah merupakan unggas liar yang telah dijinakkan dan menghasilkan keturunan, serta dipelihara oleh masyarakat Bengkulu. Penelitian ini bertujuan untuk mengetahui dan mengevaluasi manajemen pemeliharaan dan produksi peranakan ayam hutan merah yang dipelihara oleh masyarakat Bengkulu. Responden penelitian ditentukan dengan metode snowball sampling, dan diperoleh lima puluh responden. Data diperoleh melalui observasi, diskusi dan wawancara, serta pengisian formulir yang telah disiapkan; meliputi pengelolaan pakan, kandang, pencegahan penyakit, pemanfaatan dan produksi. Hasil penelitian menunjukkan bahwa keturunan RJF yang dipelihara masyarakat digunakan untuk kawin silang dengan ayam lokal (47%), produksi anakan (28%), sebagai ayam berburu (62%), dan ayam hias (82%). Ayam dipelihara dengan 4 cara: (1) dikandangkan pada siang dan malam hari, (2) ayam dibebaskan pada siang hari dan dikandangkan malam hari, (3) ayam dibebaskan pada siang dan malamnya, dan (4) ayam ditempatkan pada tenggeran. Pakan yang diberikan adalah pakan komersial (BR1), jagung, beras, beras merah, dedak, jangkrik dan telur semut. Produksi telur rata-rata 34 butir/ekor/tahun, produksi anak ayam diperkirakan 27 ekor/ekor/tahun, dan pertumbuhan populasi 2,68%/tahun. Kesimpulannya, peternakan ayam masyarakat masih bersifat tradisional, kuantitas dan kualitas pakan belum mencukupi, kandang sangat sederhana, pencegahan penyakit dan perlindungan keamanan belum memadai. Sebagai ayam lokal rata-rata produksi telurnya tinggi, daya tetas dan produksi anakannya tinggi, namun perkembangan populasinya lambat. Manajemen pemeliharaan anak ayam yang buruk dan tujuan membesarkan keturunan RJF menyebabkan perkembangan populasi menjadi lambat. Kata kunci: Komunitas, Manajemen dan Produksi, Pemeliharaan, Keturunan ayam hutan merah